Understanding membrane pore-wetting in the membrane distillation of oil emulsions via molecular dynamics simulations - Velioğlu, Sadiye (2020)
The escalating volume of oily wastewater, particularly produced water, necessitates efficient means of treatment for the recovery of both the water and oil constituents. Towards this end, membrane distillation (MD) is a promising candidate. Unfortunately, studies on the MD of oil emulsions are scarce, in large part because of membrane pore-wetting issues, which undermines the separation of oil and water. An earlier experimental study has indicated that membrane pore-wetting is caused by the presence of surfactant (namely, SDS) and salt (namely, NaCl), rather than oil, but the mechanisms underlying the poor performance remains unknown. Therefore, in order to improve the feasibility of MD, this molecular dynamics study is targeted at revealing the complex interactions that are detrimental to MD performance. The interactions of the three key constituents in produced water (namely, surfactant, oil and salt) among themselves and with the membrane are studied. The worst membrane pore-wetting experimentally observed for feeds containing SDS and NaCl is because NaCl increased the SDS-PVDF affinity without decreasing the mobility of SDS, and thereby leads to decreased surface tension and the increased likelihood of exceeding the liquid entry pressure (LEP). Accordingly, in order to mitigate pore-wetting in the membrane distillation of such feeds, means towards reducing the surfactant-membrane affinity, rather than oil-membrane affinity, and surfactant mobility near the membrane are recommended.